Acupuncture treatment of hind limb weakness in a diabetic dog with kidney yin and qi deficiency - Hizriah Alief Jainudin (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2025)
Canine diabetes mellitus (DM) is a chronic endocrine disorder characterized by persistent hyperglycemia and metabolic imbalance, frequently leading to secondary complications such as neuropathic weakness. Abrielle, an eleven-year-old female Siberian Husky, presented to the small animal clinic with hind limb weakness that had persisted for three months. The dog also showed clinical signs of polydipsia, polyuria, and weight loss, despite an increased appetite. The owner reported that the dog’s daily diet consisted mainly of white rice with very little protein. Laboratory examination revealed hyperglycemia (423 mg/dL), elevated fructosamine levels (340 µmol/L), and glucose-positive dark brown urine. Based on these findings, the dog was diagnosed with insulin-dependent diabetes mellitus. Treatment with insulin was prescribed twice daily, and acupuncture therapy was recommended to support recovery and address hind limb weakness. Abrielle underwent acupuncture twice a week using electroacupuncture, dry needles, and aqua acupuncture. After four sessions, noticeable improvement in mobility was observed, and after three months, the dog’s body weight increased from 38.5 lbs to 48.5 lbs, with a more active and friendly demeanor.